ANALISIS PENERAPAN MANAJEMEN RISIKO PADA PRODUK PEMBIAYAAN PEMILIKAN RUMAH (PPR) BSI GRIYA KCP PAYAKUMBUH - Fitri Handayani; Sandra Dewi (Jurnal Ekonomi dan Bisnis, 2024)
The background of this research aims to analyze risk management and determine the mechanism of PPR financing produkcts at BSI KCP Payakumbuh. In running its products, BSI is not limited to risks. Therefore, risk management occurs at BSI KCP Payakumbuh and is expected to minimize the risks that occur in BSI Griya PPR financing products with clear and good procedures and systematics. The research method used in this resesacrh is a qualitative method with the key informant for this research being the head of Bank Syariah Indonesia KCP Payakumbuh, the main informant is in the marketing department who is in charge of this field and the informant supports 5 customers. In collecting data, researchers used observation, interviews and documentation methods. The results of this research explain that the risk management implemented at BSI KCP Payakumbuh is carried out using 5C analysis (character, capital, collateral, capacity, and condition of economy). Meanwhile, the mechanism looks at 3 indicators, namely filing, income and financing guarantees. In implementing risk management carried out by BSI KCP Payakumbuh for BSI Griya Home Ownership Financing Products (PPR) it is also in accordance with sharia principles, this can be seen from the distribution mechanicm (PPR) of BSI Griya which is in accordance with its financing.